N-Heterocyclic Carbene Boranes as Reactive Oxygen Species-Responsive Materials: Application to the Two-Photon Imaging of Hypochlorous Acid in Living Cells and Tissues - Pak, Yen Leng; Park, Sang Jun; Wu, Di; Cheon, Bo Hyun; Kim, Hwan Myung; Bouffard, Jean; Yoon, Juyoung (Angewandte Chemie - International Edition, 2018)
N-Heterocyclic carbene (NHC) boranes undergo oxidative hydrolysis to give imidazolium salts with excellent kinetic selectivity for HOCl over other reactive oxygen species (ROS), including peroxides and peroxynitrite. Selectivity for HOCl results from the electrophilic oxidation mechanism of NHC boranes, which stands in contrast to the nucleophilic oxidation mechanism of arylboronic acids with ROS. The change in polarity that accompanies the conversion of NHC boranes to imidazolium salts can control the formation of emissive excimers, forming the basis for the design of the first fluorescence probe for ROS based on the oxidation of B−H bonds. Two-photon microscope (TPM) ratiometric imaging of HOCl in living cells and tissues is demonstrated.
Keywords: Electrophilic oxidation; Fluorescence probes; N-heterocyclic carbenes; Oxidation mechanisms; Ratiometric imaging; Reactive oxygen species; Responsive materials; Two photon microscopy; Animals; Boranes; HeLa Cells; Hippocampus; Humans; Hypochlorous Acid; Methane; Mice; Microscopy, Fluorescence, Multiphoton; Oxidation-Reduction; RAW 264.7 Cells; Reactive Oxygen Species; boron; fluorescence probes; N-heterocyclic carbenes; reactive oxygen species; two-photon microscopy